Volcanic Cloud and Aerosol Monitor (VOLCAM) for Deep Space Gateway - Krotkov, N.; Bhartia, P. K.; Torres, O.; Li, C.; Sanders, S.; Realmuto, V.; Carn, S.; Herman, Jay (My University, 2018)
Frequent (~15 min) imaging of reflected solar ultra-violet (UV) and thermal ifrared (TIR) radiation of the whole Earth from cislunar vantage point offer unique possibilities to answer NASA’s Earth System Science (ESS) questions and further advance volcanic ash (VA) and sulfur dioxide (VSO2) aviation safety applications. We propose complementary ultraviolet (UV) and ther-mal Infrared (TIR) filter cameras for a dual-purpose whole Earth imaging with complementary natural haz-ards applications and Earth System science goals.
Deep Space Gateway Science Workshop 2018 (LPI Contrib. No. 2063) This work was written as part of one of the atuthor's official duties as an Employee of the United States Government and is therefore a work of the United States Government. In accordance with 17 U.S.C. 105, no copyright protection is available for such works under U.S. Law.
Keywords: ultraviolet (UV) filter camera; Thermal Infrared (TIR) filter camera; whole earth imaging; atmospheric composition retrievals; combined use of UV and TIR cameras